Nutrient Intake, Digestibility, Rumen Parameters and Blood Metabolites of Kacang Goats Fed Silage of Forage Mixture Produced from Intercropping of Sorghum Differing in Planting Space with Butterfly Pea (Clitoria ternatea) - Hartati, E.; Lestari, G.A.Y.; Kleden, M. M.; Jelantik, I.G.N. (Indian Journal of Animal Nutrition, 2020)
An experiment was conducted to investigate the effect of feeding silage of sorghum-butterfly pea mixture which was made of forage harvested from sorghum sown at differing planting space and intercropped with Clitoria ternatea on intake, digestibility, rumen environment and blood metabolites of Kacang goats. The experiment was following a replicated latin square experiment with three treatments and three periods. In each period, two goats were randomly fed one of the three silage mixture which was made of clitoria and sorghum mixture harvested from sorghum planting space of 20x20 cm2 (S20), 40x40 cm2 (S40) and 60x60 cm2 (S60). Data on feed intake, digestibility, ruminal pH, ammonia and VFA concentrations as well as blood glucose and total plasma protein were collected during the last week of each period which lasted for three weeks.Â Results showed that crude protein content were increased with increasing sorghum planting space as the proportion of clitoria in the forage mixture increased. Meanwhile, crude fiber were comparable among different silage. Dry matter intake and digestibility were not different (P>0.05) in kacang goatsÂ fed different silage. However, rumen ammonia and VFA concentrations were significantly lower (P<0.05) in S20 compared to S40 and S60. It is concluded that there is no benefit for increasing sorghum planting space beyond 40x40 cm2 when intercropped with Clitoria ternatea.